UNSUR-UNSUR INTRINSIK CERPEN âIKTISYÄFU AL-ALÅªMUNIÅªMâ DALAM ANTOLOGI âULBATUN MIN Aá¹¢-á¹¢AFÄªá¸¤ KARYA Iá¸¤SÄN âABDU AL-QUDDÅªS: ANALISIS STRUKTURAL ROBERT STANTON - , YULIAN PRASETYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study discusses the intrinsic elements of the short story âIktisyÄfu al- AlÅ«muniÅ«mâ in the short story anthology of Ê»Ulbatun min aá¹£-á¹¢afih written by IhsÄn Ê»Abdu al-QuddÅ«s.The theory used in this short story is a structural theory. The problem discussed in this short story is intrinsic elements that are contained in the short story and its relations. The intrinsic elements that are discussed consist of theme, fact story consisting of characters and characterizations, plot, and setting, as well as the meaning of the storyâs which consists of the story's point of view and the title. The study is concluded by analyzing the relationship among the elements. The purpose of study concluded is to know the instrinsic elemnets and the relations among the elements of short story âIktisyÄfu al-AlÅ«muniÅ«mâ. The study concluded that the theme of this short story is to receive a new idea that differs with the idea known in society, struggle and sacrifice are required. The main character who carries the theme is named JamÊ»ah Ê»Abdu aá¹£-á¹¢amad, he is a man from a village who brings an alumunium to his village. The plot of this story is straight with a background of village and city. The story has background in social life of the traditional society that rejected alumunium as their equipment. This short story is told with third person point of view. Every element in this short story has relations to each other thus forming some sort of meaning.